Power Communication and the Production of Obedience in Animal Farm: A Critical Discourse Analysis - Hana Restu Pratiwi; Firly Annisa (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This study examines how power communication practices shape obedience and silence among subordinate groups through a critical discourse analysis of George Orwell’s Animal Farm. Grounded in a critical paradigm and qualitative approach, the study applies Critical Discourse Analysis by integrating Norman Fairclough’s and Teun A. van Dijk’s frameworks. The data consist of textual units including narrative structures, dialogues, slogans, and rule transformations within the novel. The findings reveal that domination in Animal Farm is not primarily sustained through physical coercion, but through symbolic communication practices that regulate meaning production, control collective memory, and normalize inequality. The consolidation of power operates through three main mechanisms: the construction of legitimacy, the normalization of inequality, and the production of obedience and silence. Obedience emerges not as mere absence of resistance, but as the outcome of value internalization and systematic restriction of critical articulation. These results underscore that the stability of domination largely depends on communication’s capacity to shape social consciousness and constrain collective thought.